Structure of Atherosclerotic Plaques in Different Vascular Territories: Clinical Relevance - Poredos, Pavel; Poredos, Peter; Jezovnik, Mateja K. (Current Vascular Pharmacology, 2018)
Background: Atherosclerosis is a systemic disease with different faces. Despite similar, or even identical, risk factors and pathogenesis, atherosclerotic lesions and their clinical manifestations vary in different parts of the vasculature. Peripheral arterial disease (PAD) in the superficial femoral artery (SFA) represents a frequent clinical manifestation of atherosclerotic disease. The pathohistological characteristics of plaques in PAD differ from lesions in the coronary arteries. Plaques in the SFA have more fibrotic elements with less lipid and degenerative tissue elements; this makes them more stable and less prone to rupture. The density of vasa vasorum, an important determinant of structure and stability of atherosclerotic lesions, is significantly lower in PAD than in coronary arteries. Further, haemodynamic forces and shear stress vary in different segments of the arterial tree and influence the development of atherosclerotic lesions and their stability. It follows that the clinical consequences differ depending on the vascular territory involved. In the coronary arteries, acute thrombotic occlusion with clinical manifestation of myocardial infarction is one of the most frequent manifestations due to unstable atherosclerotic lesions. Atherosclerotic lesions in SFA progress slowly and are more stable; therefore, clinical manifestations develop more gradually. Conclusion: The atherosclerotic process in SFA is frequently asymptomatic or presents as stable intermittent claudication, and in a relatively low percentage, progresses to critical limb ischaemia. Also, remodelling of the arterial wall in peripheral arteries compensates for the reduction of arterial lumen and provides blood flow in spite of relatively large atherosclerotic lesions. However, arterial restenosis after recanalization procedures in SFA reduces the long-term success of recanalization.
Keywords: coronary arteries